2022
DOI: 10.1038/s41598-022-12627-1
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and dose optimization of intravenous levofloxacin in hospitalized adult patients

Abstract: Although levofloxacin has been used for the last 25 years, there are limited pharmacokinetic data to guide levofloxacin dosing in adult patients. This study aimed to develop a population pharmacokinetic model of levofloxacin for adult hospitalized patients and define dosing regimens that attain pharmacokinetic/pharmacodynamic target associated with maximum effectiveness. Blood samples were drawn from 26 patients during one dosing interval. Population pharmacokinetic modelling and dosign simulations were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
4
0
2
Order By: Relevance
“…In this study, eGFR was the only covariate that had a significant impact on the model, which is consistent with the findings of Cojutti et al 15 and Setiawan et al 16 Levofloxacin is almost not metabolized in the body and is primarily eliminated through the kidneys in its unchanged form via urine. Approximately 79‐87% of the drug is eliminated in the urine 14,17,18 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, eGFR was the only covariate that had a significant impact on the model, which is consistent with the findings of Cojutti et al 15 and Setiawan et al 16 Levofloxacin is almost not metabolized in the body and is primarily eliminated through the kidneys in its unchanged form via urine. Approximately 79‐87% of the drug is eliminated in the urine 14,17,18 …”
Section: Discussionsupporting
confidence: 92%
“…Based on the results of levofloxacin dose simulations, when using levofloxacin for empirical treatment of pneumonia in the elderly, a recommended dosing regimen is 750 mg once daily. Other related studies have also shown that a dosing regimen of 750 mg once daily with levofloxacin leads to good clinical outcomes and is well‐tolerated 16,23–28 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These data indicated that the chitosan films we developed in this study could serve for localized topical use as the systemic exposure (indicated by the permeation data) is likely to be minimal, indicating good safety profiles, especially for toxic drugs such as AMB [71]. Even though there are very limited resources to define concentration toxicity threshold for levofloxacin [72,73], the safety profile of levofloxacin has been widely reported in the literature and a high daily dose of 1000 mg is recommended for patients [74]. The deposition and permeation of LVX from the film (approximately 21.54 µg in total) should be tolerable [75].…”
Section: Skin Deposition and Permeation Studies In Franz Cellsmentioning
confidence: 86%
“…С учетом нарастающей в Российской Федерации резистентности и ростом МПК 90 оптимальная доза перорального амоксициллина -750-1000 мг на прием, препарат принимается 3 раза в сутки [19,20]. При аллергии на β-лактамы надежной альтернативой являются рФХ (моксифлоксацин 400 мг, левофлоксацин не менее 500 мг 2 раза в сутки) [1,4,7,14,[18][19][20][46][47][48][49][50]. Применение левофлоксацина оправдано в случаях высокой вероятности синегнойной инфекции, например у лиц с тяжелой ХОБЛ и/или бронхоэктазами при непереносимости β-лактамов, в том числе карбапенемов.…”
Section: антибактериальная терапияunclassified